A Non-Volatile Memory Based on NbOx/NbSe2 Van der Waals Heterostructures - Ji Eun Kim; Van Tu Vu; Thi Thanh Huong Vu; Thanh Luan Phan; Young Rae Kim; Won Tae Kang; Kunnyun Kim; Young Hee Lee; Woo Jong Yu (Applied Sciences, 2020)
Two-dimensional (2D) van der Waals (vdW) layered transition metal dichalcogenides (TMDs) materials have been receiving a huge interest due to atomically thin thickness, excellent optoelectronic properties, and free dangling bonds. Especially the metallic TMDs, such as MoTe2 (1T’ phase), NbS2, or NbSe2, have shown fascinating physical properties through various applications, such as superconductor and charge density wave. However, carrier transport of metallic TMDs would be degraded due to the poor stability in ambient conditions. To date, achieving both high device performance and long-term stability is still a huge challenge. Thus, an alternative way to develop both unavoidable native oxide and metallic TMDs is under consideration for new era research. In this respect, 2D metallic TMD materials have attracted high attention due to their great potential in neuromorphic-based devices with metal-insulator-metal structures, making it possible to produce scalable, flexible, and transparent memory devices. Herein, we experimentally demonstrated a synthesized metallic NbSe2 by a chemical vapor deposition method with a highly uniform, good shape distribution and layer controller ranging from 2–10 layers. Together, for the first time, we proposed the NbOx/NbSe2 heterostructure memristor device based on the native NbOx oxide on the interface of multi-layer NbSe2 flakes. The ultra-thin native NbOx oxide of 3 nm was formed after a period of oxidation time under air condition, which acts as a memristive surface in the Au-NbOx-Au lateral memristor device, in which oxygen vacancies form a conductive filament. Our NbOx/NbSe2 hetero-tructured memristor exhibits a stable memory window, a low-resistance-state/high-resistance-state ratio of 20, and stable endurance properties over 20 cycles at a low working voltage of 1 V. Furthermore, by the retention property test, non-volatile characteristics were confirmed after over 3000 s in our best data. Through a systematic study of the NbOx/NbSe2 heterostructured memristor device, this report will open new opportunities for next-generation memory devices application.